Demographics and Histopathological Features of Laryngeal Carcinoma at Mardi Waluyo Hospital - Vatiana Satyani; Suwardi (The International Journal of Medical Science and Health Research, 2024)
Background: Laryngeal carcinoma is a malignancy arising from squamous cells of the epithelial lining of the larynx. It is one of the more common head and neck cancers, with an incidence of approximately 3.2 cases per 100,000 individuals annually worldwide. Risk factors include smoking, alcohol consumption, gastroesophageal reflux disease, exposure to chemical inhalants, and viral infections, particularly Human Papillomavirus (HPV). Objective: This study aimed to evaluate the demographic characteristics, histopathological features, and risk factors associated with laryngeal carcinoma among patients at Mardi Waluyo Hospital. Methods: This descriptive study utilized data from medical records and histopathological examinations of patients between 2018 and 2023, analyzed in January 2024 at Mardi Waluyo Hospital. Results: Among 39 patients, 34 were male (87%), and 5 were female (13%). Patients aged ≤60 years accounted for 36%, while those >60 years constituted 64%. Histopathological examination revealed squamous cell carcinoma in 34 cases (87%) and other pathologies in 5 cases (13%). Smoking history was significant: 75% had smoked for more than 10 years, while 25% smoked for less than 10 years or were non-smokers. Conclusion: Over the past five years, an average of 8 cases per year of laryngeal carcinoma were reported. Smoking was identified as the most significant risk factor. Squamous cell carcinoma was the predominant histopathological finding in patients at Mardi Waluyo Hospital.